Problematika pembelajaran matematika pada materi fungsi dan pemodelannya: Studi kasus kelas XI MAN 1 Blitar - Roisiyah, Farida Ikrimatin Sayyidah (Maliki Interdisciplinary Journal, 2024)
Mathematics is an important science in everyday life. However, mathematics is still considered difficult by the majority of students. Especially on the material of function and modelling. This affects students’ interest and understanding at the time of learning. This study aims to analyse problems in function learning and modelling in class XI MAN 1 Blitar. This type of research is a case study research with class XI-D MAN 1 Blitar. The data collection techniques used are observation and interview. Data analysis techniques in from of description analysis to explain problems in learning mathematics, function material and modelling. The results of this study show the identification of students’ difficulties in learning mathematics, function material and modelling.